Impact of Elephant Camp Induced Disturbance on Established Teak Reserves - A Study from Indira Gandhi Wildlife Sanctuary and National Park, Western Ghats, India - Prabhakaran, V.; Shankar, P. R.; Panneerselvam, S. T. (Indian Forester, 2006)
Impact of grazing pressure of 23 camp elephants on Class I teak plantations in the Indira Gandhi Wildlife Sanctuary and National Park was assessed by random quadrats of size 10mÃ—10m. The results indicate serious deterioration of the teak stand due to the debarking and death of trees by camp elephants and the resultant gaps thereby leading to invasion of weeds. The following are the recommendations (a) Periodic shifting of elephant camps with a minimum interdistance of at least 5 km; (b) Camp elephants be left farther for grazing; (c) Stall feeding for camp elephants; (d) Felling of dead teak trees and the proceeds from this sale pumped into the sanctuary for conservation efforts or for the purchase of cut fodder; (e) Utilization of the cleared areas for the cultivation of fodder species.